2016
DOI: 10.2139/ssrn.2748895
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Award Scheme in Innovation Tournaments

Abstract: In an innovation tournament, an organizer solicits innovative ideas from a number of independent agents. Agents exert effort to develop their solutions, but their outcomes are unknown due to technical uncertainty and/or subjective evaluation criteria. In order to incentivize agents to make their best effort, the organizer needs to devise a proper award scheme. While extant literature either assumes a winner-take-all scheme a priori or shows its optimality under specific distributions for uncertainty, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(100 citation statements)
references
References 15 publications
(15 reference statements)
2
98
0
Order By: Relevance
“…), feedback mechanism (Mihm and Schlapp , Wooten and Ulrich ), and incentive and award structure (Ales et al. , , Erat and Krishnan , Körpeoğlu and Cho ); see Ales et al. () for a more comprehensive review for this literature.…”
Section: Inclusive Innovation: An Operations Lensmentioning
confidence: 99%
See 1 more Smart Citation
“…), feedback mechanism (Mihm and Schlapp , Wooten and Ulrich ), and incentive and award structure (Ales et al. , , Erat and Krishnan , Körpeoğlu and Cho ); see Ales et al. () for a more comprehensive review for this literature.…”
Section: Inclusive Innovation: An Operations Lensmentioning
confidence: 99%
“…Inclusive ideation comes with its own operational challenges. For instance, in open innovation, the contest organizer has to make key operational decisions, such as duration of the tournament (Bimpikis et al 2019(Bimpikis et al , K€ orpeo glu et al 2017, transparency level of the identity of participants and submissions (Bockstedt et al 2016), feedback mechanism (Mihm andSchlapp 2019, Wooten andUlrich 2017), and incentive and award structure (Ales et al 2017, Erat and Krishnan 2012, K€ orpeo glu and Cho 2018; see Ales et al (2018b) for a more comprehensive review for this literature. In the case of technology-driven ideation, the main challenge is that such innovations are often more radical and therefore high risk (given that there is no pre-expressed need for them).…”
Section: Inclusive Product and Service Innovationmentioning
confidence: 99%
“…This line of research has focused mainly on identifying the optimal prize structure for incentivizing contest participants to do their best in crowdsourcing contests. More specifically, scholars have examined whether a fixed sum should be provided to a single winner (a winner-takes-all award structure) or whether the prize money should be distributed among various participants (i.e., a multiple-prize award structure) (e.g., Ales et al 2017;Terwiesch and Xu 2008). Terwiesch and Xu (2008) found, for example, that for ideation projects (the type which we focus on in this paper), a winner-takes-all structure is the best strategy.…”
Section: Monetary Rewards In Crowdsourcingmentioning
confidence: 99%
“…Terwiesch and Xu (2008) found, for example, that for ideation projects (the type which we focus on in this paper), a winner-takes-all structure is the best strategy. Ales et al (2017), however, showed that multiple prizes may work better than winner-takes-all prizes in certain circumstancesas, for example, when the crowd perceives that popularity with consumers is important in assessing ideas (which is often the case, as most crowdsourcing initiatives allow and indeed encourage other consumers to vote on the ideas put forward-e.g., Lego Ideas, BDo Us A Flavor^contest). As a whole, although this research extended our understanding of how prize money should be distributed among winners in crowdsourcing contests, it did not answer the question as to what role the presence and size of monetary rewards play in driving the generation of creative ideas.…”
Section: Monetary Rewards In Crowdsourcingmentioning
confidence: 99%
“…Taylor (), Che and Gale (), and Ales et al () are examples that analyze the relationship between contest design and effort from participants. Hvide and Kristiansen (), Gilpatric (), and Suzuki () are examples that analyze the relationship between contest design and risk‐taking from participants.…”
Section: Related Literaturementioning
confidence: 99%